Pengembangan Usaha Bumdes Jejama Usaha melalui Tiktok, Literasi Keuangan, dan Program Kerja - Fitra Dharma; Yenni Agustina; Roslina Roslina (Penerbit Goodwood, 2023)
Purpose: Bumdes has a crucial role for village to increase the villager's wealthy. Therefore, Indonesia's government encourage all parts to give their best can do to evolve the bumdes. The purpose of this service activity is to increase the knowledge and skills of trainees in branding positioning by using social media tiktok, financial literacy, and preparing work programs. Methodology: The methods which we use for transferring knowledge are persuasive methods and training. We considered these methods appropriate to overcome the problem that they have. Results: There was an increase in the participants' knowledge, understanding, and skills in branding positioning through tiktok media, financial literacy, and preparing work programs. This increase has had a positive impact on the progress of the Jejama Usaha BUMDES in its business activities. This activity also provides output in the form of links and tiktok content for culinary tourism in the village of bumdes jejama usaha. Conclusions: Training in branding positioning, financial literation, and work program can assist the business entities belonging to the village of Jejama Usaha to minimize the obstacles. Thus, village-owned enterprises can continue to progress and develop even better. Limitations: The implementation of this activity certainly has limitations, namely in terms of facilities and infrastructure. Disturbances in the LCD system certainly gave the team a few obstacles to deliver material in a timely manner. Thus, the disturbance resulted in a delay in the implementation of the next session's activities. The next limitation is that most of the participants present are at an age that is less adaptive to technology, which of course is a challenge for the team to assist in the use of digital technology such as tiktok. Contribution: This technology can help the BUMDes to increase their income.